TEACHING READING TO THE STUDENTS: STRATEGIES AND SIGNIFICANCE - Djalilov M.M. (American Journals Publishing, 2024)
This article explores the importance of teaching reading, key approaches to instruction, and the role of educators in fostering literacy.
Keywords: Reading, strategy, instruction, literacy, teaching.